Physical review records
Primarily correspondence of Gregory Breit and John Tate as editors of the periodical Physical Review concerning attempts of U.S. scientists to impose voluntary restrictions on the publication of scientific papers relating to nuclear fission and other classified scientific information during Wor ld War II. Correspondents include Lyman J. Briggs, J.W. Bucha, Arthur Compton, James B. Conant, Enrico Fermi, Wendell Furry, Glenn T. Seaborg, Leo Szilard, and Harold Urey.
Collection material in English.
Keywords: Breit, Gregory, -- 1899- -- Correspondence; Briggs, Lyman J. -- 1874-1963 -- Correspondence; Bucha, J. W. -- Correspondence; Compton, Arthur Holly, -- 1892-1962 -- Correspondence; Conant, James Bryant, -- 1893-1978 -- Correspondence; Fermi, Enrico, -- 1901-1954 -- Correspondence; Furry, W. H. -- 1907- -- Correspondence; Seaborg, Glenn Theodore, -- 1912- -- Correspondence; Szilard, Leo -- Correspondence; Tate, John T. -- 1889-1950 -- Correspondence; Urey, Harold Clayton, -- 1893- -- Correspondence; Nuclear fission; Physics -- Periodicals; World War, 1939-1945 -- Censorship